Study on the Assessment of the Level of Skill and Coordination of Higher Education Students - C.G. Catuna; I.M. Butu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The research was conducted in the first semester of the academic year 2023-2024, the subjects tested were students of the Faculty of Physical Education and Sport of “Spiru Haret” University of Bucharest. They gave their consent to participate in tests on the evaluation of skills in handball, gymnastics, and tennis classes. So in gymnastics, they performed circle throws and fixed-point ball throws over time, with correct execution being appreciated. The throws with the two objects were made with both hands, starting with the handy hand, with a break between trials. In tennis, our subjects had 10 balls thrown to them by the teacher and had to perform the long forehand crosscourt shot in the hatched areas (as the first trial) and the long backhand crosscourt shot in the hatched areas (the second trial). For handball, we opted in this experimental study for two individual trials of moving with two balls in dribbling over a distance of 10m, dribbling simultaneously (trial 1) and alternately (trial 2), and a partner passing trial (distance 3-4m, 30seconds) simultaneously with (trial 3).